Metro traction power measurements sizing a hybrid energy storage system utilizing trains regenerative braking. (January 2023) - Leoutsakos, G.; Deloukas, A.; Sarris, K.; Apostolopoulos, I.; Mamaloukakis, C.; Kyriazidis, D.; Bensmann, A.; Hanke-Rauschenbach, R.
Abstract: The paper describes the measuring systems and methodology for acquiring traction power measurements on the on-board traction systems of two metro trains and three 750 V DC rectifier substations in the Athens Metro Line 2. Being part of a wider investigation to develop a Hybrid Energy Storage System (HESS), the purpose of the present measurements is to provide traction systems experimental and operational data that would assist in the understanding of the dynamic characteristics of train braking regeneration and quantify the available energy that could be stored in a super-capacitors/batteries hybrid storage system for further use, which would otherwise be wasted and consumed as heat in stations and tunnels through the trains' braking resistors. In turn the stored energy could power upon demand selected stationary electrical loads in Metro stations of a non-safety critical character (such as lighting, ventilation, pumps, etc.) leading to very significant energy savings and to a corresponding reduction of greenhouse gases. Preliminary results confirm the feasibility of the energy saving concept indicating a significant potential for the hybrid energy storage devices and subsequent energy re-use of 4000–6000 kWh/day per rectifier substation of otherwise unused train braking energy, with a typical Metro station stationary loads consumption of 2000 kWh/day. Highlights: Methodology described for traction power measurements on train onboard traction systems & 750 VDC rectifier substations in Athens Metro Line 2. Hybrid Energy Storage System (HESS) development, storing train braking regenerated energy in supercapacitors/batteries in Metro stations. Energy stored used on Metro station electrical loads e.g. lighting/ventilation/pumps/etc. or for other public uses (e.g. street lighting). Field measurements based energy storage system design with proven feasibility. Energy re-use of train braking energy using HESS, of 4-6 MWh/day per rectifier substation, with typical Metro station consumption of 2 MWh/day.